2015
DOI: 10.1055/s-0035-1554521
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Ethnic Variation in Radiographic Disability Thresholds: Analysis of North American and Japanese Operative Adult Spinal Deformity Populations

Abstract: Introduction Regression analysis of adult spinal deformity (ASD) databases in North America (NA) has yielded radiographic disability thresholds for sagittal vertical axis (SVA), pelvic tilt (PT), and pelvic incidence to lumbar lordosis (PI–LL), which have been used in formulating the Schwab–SRS ASD classification. These thresholds are often used as correction goals for surgery planning, but it is unclear whether these thresholds vary in other geographic regions or ethnicities. This is the first comparison of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…6 Furthermore, ethnic variations between health-related quality-of-life measures and radiographic parameters in the setting of ASD have also been reported, suggesting the need for population-adjusted sagittal modifiers in the management of ASD. 20 …”
Section: Discussionmentioning
confidence: 99%
“…6 Furthermore, ethnic variations between health-related quality-of-life measures and radiographic parameters in the setting of ASD have also been reported, suggesting the need for population-adjusted sagittal modifiers in the management of ASD. 20 …”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that spinopelvic parameters differ between races, with Asians having a greater compensatory mechanism in the thoracic spine and pelvis compared with that in the Western population [23,24]. Spinal alignment changes with age, and PT, PI-LL mismatch, and SVA all increase.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, just single-level ACDF was involved in our study so that we cannot take the number of ACDF levels into discussion. Fifth, the effect of ethnicity on the sagittal alignments of the cervical spine was not taken into consideration so that our results may be not globally generalizable 23 . Last but not least, our study did not include lateral radiographs of the full spine, and the relationship between postoperative dysphagia and other global sagittal parameters, such as thoracolumbar alignments, could thus not to be discussed 10 .…”
Section: Discussionmentioning
confidence: 99%